Professionalization and academic development - Rydbeck, Kerstin (2004)
The aim of this paper is to glimpse the situation and characteristics of the library and information science career at Uppsala University in Sweden, the labour market opportunities for graduates of that institution and also a vision of the future from the perspective of the faculty.